2012
DOI: 10.1002/jcb.24315
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of PTEN expression and activity by angiotensin II induces proliferation and migration of vascular smooth muscle cells

Abstract: PTEN (phosphatase and tensin homolog deleted on chromosome 10) is a tumor suppressor and has been suggested recently to be involved in the regulation of cardiovascular diseases. The molecular mechanisms of this regulation are however poorly understood. This study shows that down regulation of PTEN expression and activity by angiotensin II (Ang II) increased proliferation and migration of vascular smooth muscle cells (VSMCs). The presence of Ang II induced rapid PTEN phosphorylation and oxidation in accordance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…Angiotensin II is a strong stimulator for proliferation and migration of VSMCs and participates in the process of atherosclerosis and vascular stenosis. [26][27][28] In agreement with those studies, our results show that angiotensin II increases the proliferation and migration of VSMCs. Meanwhile, 100 µM naringenin can inhibit angiotensin II-induced proliferation, and migration.…”
Section: Discussionsupporting
confidence: 93%
“…Angiotensin II is a strong stimulator for proliferation and migration of VSMCs and participates in the process of atherosclerosis and vascular stenosis. [26][27][28] In agreement with those studies, our results show that angiotensin II increases the proliferation and migration of VSMCs. Meanwhile, 100 µM naringenin can inhibit angiotensin II-induced proliferation, and migration.…”
Section: Discussionsupporting
confidence: 93%
“…It has been demonstrated that environmental factors, such as PDGF, endothelin, transforming growth factor, and inflammatory mediators, can induce synthetic smooth muscle cell phenotypic differentiation (24). AngII is a well-documented activator of VSMC proliferation and migration, which promotes atherosclerosis and vessel stenosis (25)(26)(27). Here, we showed that resveratrol inhibited AngII-induced proliferation and migration in A7r5 cells.…”
Section: Discussionmentioning
confidence: 58%
“…This may be relevant since we previously demonstrated that early trauma-induced SMC apoptosis results in increased late neointima formation [10]. At later time points, apoptosis seems to be confined to SMC of the developing neointima and, therefore, may be beneficial by limiting lesion growth [30], [31], [32]. However, PTEN-activation by therapeutic means should not follow instantly after vascular dilatation but should be applied at later time points to prevent initial exacerbation of apoptosis-induced vessel injury.…”
Section: Discussionmentioning
confidence: 99%